Implementation of Game-Based Learning Methods to Increase Student Activeness in Islamic Religious Education Subjects at SMPN 33 Merangin - Intan Putri Sasmita; M. Thontawi (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to improve students’ learning activeness through the implementation of the Game-Based Learning method in Islamic Religious Education for seventh-grade students at SMP Negeri 33 Merangin. The research employed Classroom Action Research (CAR) consisting of two cycles, including planning, action, observation, and reflection stages. The research subjects were seventh-grade students. Data were collected through observation, interviews, and documentation, and analyzed using descriptive qualitative methods. The results indicate that the implementation of Game-Based Learning significantly improves students’ activeness. Initially, students’ participation was low; however, it increased in the first cycle and became more optimal in the second cycle. This improvement is reflected in students’ active involvement in asking questions, participating in discussions, and engaging in learning activities. Therefore, Game-Based Learning is proven to be an effective method in enhancing students’ learning activeness in Islamic Religious Education